ANALYSIS OF THE SUITABILITY OF PHYSICAL DEVELOPMENT OF THE CITY TOWARDS SPATIAL PLANNING IN PEKANBARU CITY - Aini, Aisyah Nur; Ahyuni (JGE (Jurnal Geofisika Eksplorasi), 2025)
Pekanbaru City is one of the cities appointed as a National Strategic Area. Therefore, urbanization and changes in land use occur in Pekanbaru City. This study aims to decide on land-use changes, obtain information on the direction of physical development in Pekanbaru City, and decide the suitability between physical development and the Pekanbaru City spatial planning plan. The method used in this study is quantitative descriptive, digitizing on screen to make land use maps and overlaying in 2017 and 2023 to see changes in land use. The direction of physical development is obtained using a standard deviational ellipse. The suitability of land use with RTRW was obtained using the intersect overlay method.  The results of this study are 1) Changes in land use between 2017 and 2023 are dominated by settlements, industrial areas, and trade and services. For other land uses, there are also changes but not too significant. 2) The direction of physical development from the city center to the suburbs with a south and southwest direction. 3) The suitability between physical development and the Pekanbaru City Spatial Plan 2020 - 2040, as much as 33,6% is by the RTRW. Areas that are not following the RTRW are 63%. For areas that do not follow the RTRW, the figure is 3,4%. The conclusion of this study shows that most areas in Pekanbaru City have not been realized by the Pekanbaru City RTRW 2020-2040. With the increase in population, it is hoped that development will be achieved through the established development plan.